Constructing solidarity economy-based livelihoods - Esteves, A. (Museum International, 2019)
How can museums contribute to the development of commons-based livelihoods? This article explores this question by expanding the concept of museum beyond its classical roles of conservation and exhibition of significant artefacts for cultural and educational purposes, entering functions and fields of activity normally identified with those of marketspaces. This conceptual exploration includes spaces which self-identify as museums but were created to support specific areas of economic activity, as spaces of performance and promotion of identities and practices, as well as commercialization. It also includes public spaces which blur the boundary between museum and marketspace, by combining the functions of conserving and displaying material and immaterial cultural heritage with that of being spaces of production and transaction of goods and services which represent such heritage. Based on a literature review, illustrated by two case studies in Portugal, Ecomuseu de Barroso and Cooperativa Terra Chã, this article explores how hybrid public spaces which fulfil the functions of museum and marketspace politically legitimize and promote the economic sustainability of commons-based practices of production, build synergies and economies of scale between such practices, and connect their promoters with the wider public. By promoting commons-based practices of production which were marginalized by the logic of capitalism and bureaucratic governance, they become social spaces where participating producers and consumers formally and informally build trust with cooperative practices of production, distribution and commercialization. They are also spaces of mobilization of symbols and practices of belonging, as well as promotion of grassroots leadership.